Clown Teachers and the Circus of Education: The Role of Educators and the Evolution of Educational Curricula - Al-Mutairi, Musaed A (Advances in Social Sciences Research Journal, 2024)
The article "Clown Teachers and the Circus of Education: The Role of Educators and the Evolution of Educational Curricula" critiques the rigid and outdated nature of current educational curricula, using a circus metaphor to highlight the performative aspect of teaching within these constraints. It explores standardised curricula’ historical context, examining their rationale and the disconnect between these predetermined frameworks and contemporary societal needs. The analysis reveals how current curricula often fail to prepare students for the modern job market, supported by case studies and expert opinions. The challenges educators face in balancing adherence to outdated curricula with fostering genuine learning are highlighted through testimonials. The impact on students, including psychological and developmental effects, is discussed, emphasising the consequences of an exam-focused education system. The article advocates for curriculum reform, presenting successful examples and recommendations from theorists and policymakers. Innovative educational approaches are showcased, illustrating technology integration and experiential learning. The conclusion underscores the need for evolving educational practices to balance examination success with fostering genuine learning.